The Antiviral Effect of Novel Steroidal Derivatives on Flaviviruses - Zhang, Luping; Zhou, Dengyuan; Li, Qiuyan; Zhu, Shuo; Imran, Muhammad; Duan, Hongyu; Cao, Shengbo; Ke, Shaoyong; Ye, Jing (Frontiers in Microbiology, 2021)
Flaviviruses are the major emerging arthropod-borne pathogens globally. However, there is still no practical anti-flavivirus approach. Therefore, existing and emerging flaviviruses desperately need active broad-spectrum drugs. In the present study, the antiviral effect of steroidal dehydroepiandrosterone (DHEA) and 23 synthetic derivatives against flaviviruses such as Japanese encephalitis virus (JEV), Zika virus (ZIKV), and Dengue virus (DENV) were appraised by examining the characteristics of virus infection both in vitro and in vivo. Our results revealed that AV1003, AV1004 and AV1017 were the most potent inhibitors of flavivirus propagation in cells. They mainly suppress the viral infection in the post-invasion stage in a dose-dependent manner. Furthermore, orally administered compound AV1004 protected mice from lethal JEV infection by increasing the survival rate and reducing the viral load in the brain of infected mice. These results indicate that the compound AV1004 might be a potential therapeutic drug against JEV infection. These DHEA derivatives may provide lead scaffolds for further design and synthesis of potential anti-flavivirus potential drugs.